2013
DOI: 10.1088/1748-3182/8/1/016005
|View full text |Cite
|
Sign up to set email alerts
|

Swimming near the substrate: a simple robotic model of stingray locomotion

Abstract: Studies of aquatic locomotion typically assume that organisms move through unbounded fluid. However, benthic fishes swim close to the substrate and will experience significant ground effects, which will be greatest for fishes with wide spans such as benthic batoids and flatfishes. Ground effects on fixed-wing flight are well understood, but these models are insufficient to describe the dynamic interactions between substrates and undulating, oscillating fish. Live fish alter their swimming behavior in ground ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 36 publications
6
48
3
Order By: Relevance
“…The finding that wall effect can enhance cruising speed is in consistency with the results from Quinn et al [11] and FernandezPrats et al [12], where free-swimming experiments were conducted on flexible pitching (or plunging) foils near a solid boundary. However, the current finding is in contrast with that from Blevins and Lauder [13], where almost no gain in the cruising speed was found in a stingray-inspired robotic model swimming near the substrate. As to the propulsive efficiency, it seems that inconsistency exists between our finding and that of Quinn et al [11], where the propulsive economy was found to be unaffected by the presence of a solid boundary.…”
Section: Wall Effect On Propulsive Performancecontrasting
confidence: 99%
“…The finding that wall effect can enhance cruising speed is in consistency with the results from Quinn et al [11] and FernandezPrats et al [12], where free-swimming experiments were conducted on flexible pitching (or plunging) foils near a solid boundary. However, the current finding is in contrast with that from Blevins and Lauder [13], where almost no gain in the cruising speed was found in a stingray-inspired robotic model swimming near the substrate. As to the propulsive efficiency, it seems that inconsistency exists between our finding and that of Quinn et al [11], where the propulsive economy was found to be unaffected by the presence of a solid boundary.…”
Section: Wall Effect On Propulsive Performancecontrasting
confidence: 99%
“…Third, batoids are increasingly serving as subjects for robotic models of aquatic propulsion (e.g. Blevins and Lauder, 2013;Cloitre et al, 2012;Dewey et al, 2012;Krishnamurthy et al, 2010;Moored et al, 2011a,b;Park et al, 2016), and yet threedimensional biological data on how the wing moves are extremely limited. Such data are needed to provide a template for programming robotic ray wing surface motions, and we aim to provide a new kinematic data set on wing-based aquatic propulsion for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Digital movies of flow over the foils were obtained using a Photron PCI-1024 high-speed video camera (Photron Inc., San Diego, CA, USA; 1024×1024 pixel resolution). DPIV images were recorded at a sample rate of 1000 Hz and were analyzed with DaVis 7.2 software (LaVision Inc., Goettingen, Germany) as in our previous research (Blevins and Lauder, 2013;Quinn et al, 2014;Wen and Lauder, 2013).…”
Section: Analysis Of Foil Static Drag and Self-propelled Swimmingmentioning
confidence: 99%